EFEKTIFITAS NEPHROPROTEKTOR EKSTRAK RUMPUT LAUT MERAH (Eucheuma cottonii) PADA MENCIT YANG DIINDUKSI DENGAN LOGAM BERAT TIMBAL - Giftania Wardani Sudjarwo; Nuraini Farida (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2021)
This study aimed to determine the effect of the red seaweed extracts on levels of SGOT and SGPT serum mice exposed to lead per oral. The sample used were 50 male divided into 5 groups: negative control (mice were given daily with CMC /carboxy methyl cellulose 0.5 %) ; positive control (mice were given daily with CMC 0.5 % and lead 20 mg/kg BW orally once in a day for 10 days); and the treatment group ( mice were given the red seaweed extracts 200 mg; 400 mg; 800 mg/kg BW orally once daily for 28 days and lead 20 mg/kg BW on 7 th day, one hour after red seaweed extracts administration during 21 days. On day 14 measured levels of MDA, SGOT and SGPT. Data were analyzed by one-way ANOVA, followed by LSD test. The results showed that oral administration of lead acetate 20 mg/kg BW for 21 days resulted in a significant increase in SGOT, SGPT and MDA level. Treatment with red seaweed extracts 800 mg/kg BW significantly (P< 0.05) decreased the elevated SGPT, SGOT and MDA levels, compared to positive control. It can be concluded that the red seaweed extracts have a nephrotoprotective activity against lead acetat induced hepatotoxicity in mice